Viscoelastic liquid from regenerated silk fibroin in the silk i conformation: a writeable and shapeable material - Kumar, Raj; Joseph, Emmanuel; Chaudhari, Atul; Nisal, Anuya; Sharma, Kamendra P. (ACS Applied Polymer Materials, 2022)
Regenerated silk fibroin (RSF) has acquired enormous attention because of its exceptional toughness, strength, and biocompatible nature. These properties make RSF a potential candidate for the fabrication of different types of materials. However, processing even a dilute aqueous solution of RSF leads to a conformational transformation from a random coil/helix-rich (silk I) to a beta-sheetrich (silk II) state. As a consequence, RSF tends to form aggregates and loses its toughness. Working in a direction to address this problem, an aqueous solution of regenerated silk fibroin has been modified with a dual layer of polyethylenimine (PEI) and a PEG-based polymer surfactant (PS). Upon freeze-drying, the RSF-polymer complex forms a solvent-free RSF bioconjugate system and exhibits a soft solid to liquid melting transition at similar to 45 degrees C. The sequential modification with PEI and PS preserves the native-like random coil conformation of RSF up to at least 8 months of storage by not allowing interchain interactions that can lead to aggregation. Rheological and small-angle X-ray scattering measurements show that the solvent-free system is viscoelastic and exhibits a higher order microstructure mediated by the packing of the PS chains, respectively. Temperature-dependent soft solid-liquid-like dual behavior offers applications in injection-based writing, compression molding, and shaping RSF bioconjugates into various types of geometries. Furthermore, the mechanical properties of the RSF bioconjugate system can be modulated by crosslinking with glutaraldehyde vapor at 50 degrees C.
Keywords: RSF liquid; RSF soft solid; silk I conformation; silk liquid; viscoelastic